2016
DOI: 10.22610/imbr.v8i2.1274
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Commitment-based HR Practices and Organizational Performance: The Role of Organizational Learning Capabilities as a Mediator

Abstract: This study intends to investigate the relationship between commitment-based human resource practices (CBHRP) and organizational performance of the multi-national organizations in Malaysia with the present of organizational learning capability (OLC) as the mediator. The data were collected from 150 multi-national organizations, using a survey questionnaire. The returned response rate was 97 percent. A relevant statistical analytical such as regression analysis was used to test the hypotheses set forth in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…CBHRPs CBHRPs focus on a combination of HR policies and procedures that stimulate organizational members to exercise a high degree of discretion through coordinating their interests with those of the organization and establishing reciprocally strengthening high-input employeremployee relationships (Delery and Doty, 1996). CBHRPs consist of various specific practices; nonetheless, scholars share the view that three components are indispensable: a fair internal recruitment and selection process (selection practice), performance-based group compensation (incentive practice), and extensive training and development opportunities (training and development practice) (Collins and Smith, 2006;Li Chia et al, 2016). The fair recruitment and selection process prioritizes growth opportunities for existing employees over external candidates that fit the requirements of the position.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…CBHRPs CBHRPs focus on a combination of HR policies and procedures that stimulate organizational members to exercise a high degree of discretion through coordinating their interests with those of the organization and establishing reciprocally strengthening high-input employeremployee relationships (Delery and Doty, 1996). CBHRPs consist of various specific practices; nonetheless, scholars share the view that three components are indispensable: a fair internal recruitment and selection process (selection practice), performance-based group compensation (incentive practice), and extensive training and development opportunities (training and development practice) (Collins and Smith, 2006;Li Chia et al, 2016). The fair recruitment and selection process prioritizes growth opportunities for existing employees over external candidates that fit the requirements of the position.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Moreover, Pillai (2016) found that HRMP such as training and development, reward and recognition, performance appraisal and team working contribute to knowledge sharing in the organization. Mansouri (2016) and Chia et al (2016) showed that commitment-based HRMP oriented toward "committing" the human resources toward the organization as against "controlling" them, generate superior performance in the long term.…”
Section: Human Resource Management Practicesmentioning
confidence: 99%
“…In the human resource literature, a number of scholars have researched on OL-CAP as the black box and its effect on organizational performance (Asgari and Amirnezhad, 2015; Chia et al, 2016;Jerez-G omez et al, 2019). Muafi and Uyun's ( 2018) study shows that OL-CAP mediates the effect of Islamic HRM practices on environmental, social and religious performance.…”
Section: Organizational Learning Capability and Firm Performancementioning
confidence: 99%